2019
DOI: 10.3889/oamjms.2019.392
|View full text |Cite
|
Sign up to set email alerts
|

The Naturalness of Biological Movement by Individuals with Autism Spectrum Conditions: Taking Neurotypical Individuals’ Viewpoint

Abstract: BACKGROUND:When an action is being observed, it is matched to the observer’s internal representation of the action. The more similar, the more the action is perceived as natural. A factor influencing judgement of naturalness is the kinematic features of a movement. However, these features could be altered due to certain conditions that can modify movement such as Autism Spectrum Disorders. As a result, neurotypical observers may fail to interpret the action due to impaired naturalness.AIM:This work aims to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, the extent to which looking at mouths would affect how someone feels they are being looked at, and potentially related feelings of rapport, is unclear; if nonautistic people view this behavior as unnatural, it may negatively impact their perception of the autistic person. 44 , 45 Second, participants were not blind to others' diagnostic status. As in some real-world contexts, diagnostic status may be known (e.g., speaking with a family member) and in others it may be unknown (e.g., asking a stranger a question), it will be important to replicate the study with participants unaware of their partner's diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extent to which looking at mouths would affect how someone feels they are being looked at, and potentially related feelings of rapport, is unclear; if nonautistic people view this behavior as unnatural, it may negatively impact their perception of the autistic person. 44 , 45 Second, participants were not blind to others' diagnostic status. As in some real-world contexts, diagnostic status may be known (e.g., speaking with a family member) and in others it may be unknown (e.g., asking a stranger a question), it will be important to replicate the study with participants unaware of their partner's diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“… 50–52 This potential effect may reduce mutual gaze and backchanneling use more so than in casual conversation; thus, it may be interesting to explore other interaction contexts. There are also several other potential markers worth analyzing, such as facial expressions, hand gestures, interruptions, postural mirroring, word repetition, prosody, repair sequences, coherence of conversational turns, sudden movements, and general interpersonal synchrony, 10 , 44 , 45 , 53 which were excluded from this study as they were either too sparse in the available footage or would require more advanced technology to be measured effectively. We hope that these questions can be addressed in future studies of a larger scale.…”
Section: Discussionmentioning
confidence: 99%
“…This has been further supported by recent research in the social sciences that demonstrate the ways in which non-autistic people struggle to correctly infer autistic affective and mental states (e.g. Brewer et al, 2016;Edey et al, 2016;Heasman and Gillespie, 2017;Hubbard et al, 2017;Sheppard et al, 2016) and have a tendency to form negative thin-slice judgements about autistic people that can influence their desire to interact with them (Aransih, Edison and Penton, 2019;Morrison et al, 2019a;Sasson et al, 2017). Combined with research that has shown the ways in which autistic people experience high levels of mutual understanding and communicative effectiveness when interacting with other autistic individuals (e.g.…”
Section: Theory Of Mind and Similar Mindsmentioning
confidence: 76%
“…Moreover, given that both action and perceptual feedback are integral for the accurate production of movements, it is likely that the motoric differences in individuals with ASD also alter their interpretation of social movements. The mechanism for such an impairment is posited to occur via a mismatch between the perception of movements and the observer’s internal representation of those movements ( Aransih and Edison, 2019 ). For example, Gowen has proposed that many of the observed deficits in imitation in autism can be attributed to autistic children and adults failing to attend to relevant kinematic information that provides cues regarding intentionality and goals ( Gowen, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Motoric differences can also alter the production of the dynamic, moment-to-moment behavior that is integral to social communication (e.g., Brewer et al, 2016 ; Cook, 2016 ; Aransih and Edison, 2019 ; Bokadia et al, 2020 ). However, investigation of such behavior topography requires analysis at what has been described the microlevel of social interactions (e.g., Whyatt, 2017 ).…”
Section: Introductionmentioning
confidence: 99%